Paintings at the Art Institute of Chicago highlights of the collection (Art Institute of Chicago, 2017)
"The Art Institute of Chicago houses an extraordinary collection of objects from diverse places, cultures, and time periods. This catalogue opens the doors of the museum to readers, presenting an expansive selection of painted works from around the globe, introduced insightfully by James Rondeau, president and director of the Art Institute. New color photography accompanies entries written by a team of curators, art historians, and educators, which put the works into context. The book showcases a dazzling range of paintings, including an Egyptian funerary stela, an ancient Mexican wall mural, Chinese scroll paintings, Japanese painted screens, and works by artists such as Caillebotte, Cassatt, El Greco, Gauguin, Homer, Hopper, Johns, Lichtenstein, Matisse, Mitsuoki, Monet, Morisot, Motley, O'Keeffe, Picasso, Pollock, Rembrandt, Richter, Rubens, Sargent, Seurat, Tiepolo, Turner, Van Gogh, Warhol, Whistler, and Wood; contemporary artists featured include Kerry James Marshall, Wanda Pimentel, and Kazuo Shiraga"-- Provided by publisher.